2005
DOI: 10.1373/clinchem.2005.052738
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Relationships between Serum Apolipoprotein B and Serum Lipid Distributions

Abstract: Background: Apolipoprotein B (apo B) has been reported to be a better predictor of coronary artery disease than cholesterol indices. The objectives of this study were to evaluate concordances/discordances between cholesterol indices and apo B and to assess the factors that influence them. Methods: For this study, 11 816 individuals (6965 males, 4851 females), none of whom had a past history of coronary artery disease, were selected from among visitors to the health promotion center at Kangbuk Samsung Hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 24 publications
2
14
1
Order By: Relevance
“…However, the apo-A-I findings disagree with those of Abdel Ghany et al, (32) and Zhang et al, (44), as they reported decreased levels of apo-A. However, the increased apo-A-I and apo-B in NS could be explained by the hypothesis that changes in plasma oncotic pressure following hypoalbuminemia and may be involved in stimulating the transcription of a group of liver secreted proteins (38,45).…”
Section: Serum Levels Of Total Cholesterol (Tc) Low-density Lipoprmentioning
confidence: 66%
“…However, the apo-A-I findings disagree with those of Abdel Ghany et al, (32) and Zhang et al, (44), as they reported decreased levels of apo-A. However, the increased apo-A-I and apo-B in NS could be explained by the hypothesis that changes in plasma oncotic pressure following hypoalbuminemia and may be involved in stimulating the transcription of a group of liver secreted proteins (38,45).…”
Section: Serum Levels Of Total Cholesterol (Tc) Low-density Lipoprmentioning
confidence: 66%
“…In our previous review (3) we summarized these results from Stewart et al (125), Korean studies (126)(127)(128) and studies from India (129) and Canada (130). In these papers the highest values for the apo-ratio were found in those who had most manifestations of the MetS.…”
Section: Metabolic Syndrome (Mets) and Diabetesmentioning
confidence: 99%
“…In fact, the apo-ratio has also been found to be a valuable summarizing index of lipid-abnormalities and their complications in a large number of studies of the MetS and/or diabetes (125)(126)(127)(128)(129)(130)(131)(132)(133)(134)(135)(136)(137)(138)(139)143,144). In addition, the apo-ratio values are also increased in patients with hypertension, obesity, in pubertal children and in those with heredity for CV diseases (130,141).…”
Section: Relations To Atherosclerosismentioning
confidence: 99%
“…Phospholipids were measured according to their phosphorus content ( 29 ) following lipid extraction. ApoA-I was measured by a rate nephelometry method using the IMMAGE® immunochemistry system (Beckman Coulter, Villepinte, France), which is widely spread ( 30 ).…”
Section: Methodsmentioning
confidence: 99%
“…We fi rst evaluated the effects of varying FF concentrations (5,10,20,30,40, and 50%, v/v in modifi ed B2 medium) on spermatozoa hyperactivation process after 5 min of incubation at 37°C ( Fig. 1A ).…”
Section: Effects Of Ff or Hdl On Kinetics Of Spermatozoa Hyperactivationmentioning
confidence: 99%